Quality and reliability evaluation of pancreatic cancer-related video content on social short video platforms: a cross-sectional study - Yuting Lei; Foqiang Liao; Xin Li; Yin Zhu (BMC Public Health)
Abstract Background Pancreatic cancer (PC) has become one of the leading causes of cancer-related deaths worldwide. Social media platforms are widely used for health information dissemination because of their visual appeal and entertainment value. This study evaluates the content, quality, and reliability of PC-related information on domestic short video platforms. Methods A total of 265 PC-related videos were retrieved from three short video-sharing platforms: TikTok, Bilibili, and Kwai. The Global Quality Scale (GQS) and the modified DISCERN score were employed to evaluate the quality and content of the videos, respectively. Correlation analysis was conducted to explore the relationships between different video variables. Results The overall quality of the video content was low, with median scores of 2 (IQR: 2–3) for both the GQS and the modified DISCERN score. Most of the videos related to PC were posted by healthcare professionals (219/265, 82.6%). Videos from specialists received more likes on short social video platforms than those from nonspecialists did (median: 678 vs. 270, P = 0.005). Educational videos scored highest in both the GQS (median: 3, IQR 2–3) and the modified DISCERN score (median: 2.5, IQR 2–3). There was a positive correlation between GQS and video duration (r = 0.31, P < 0.01) and the modified DISCERN score (r = 0.434, P < 0.001). Conclusion The quality and reliability of the videos on these platforms were generally unsatisfactory in terms of source and content. Videos produced by healthcare professionals or institutions are more informative in terms of comprehensiveness, quality of information, and reliability than are those produced by non-healthcare professionals.